NAMP: Neighbor Aware Multicast Routing Protocol for mobile ad hoc networks - Pathan, Al-Sakib Khan; Monowar, Mostafa; Rabbi, Md.; Alam, Muhammad; Hong, Choong Seon (Zarqa University, Jordan, 2008)
A Mobile Ad Hoc Network (MANET) represents a system of wireless mobile nodes that can freely and dynamically self-organize into arbitrary and temporary network topologies without the presence of any fixed communication infrastructure. Reliable routing and robustness of the network are two important issues for MANETs. In this paper we propose Neighbour Aware Multicast Routings Protocol (NAMP), which is a tree based, hybrid multicast routing protocol for ad hoc networks. Our routing protocol aims at achieving robustness in the ad hoc networks as well as the improvement of the end-toend delivery of data packets. For route creation, the protocol uses neighboring information and dominant pruning approach. It uses secondary forwarder method for route maintenance.